Fin whale collision in the Canary islands: a pathological study - Méndez, Mariña; Espinosa De Los Monteros Y Zayas, Antonio; Arbelo Hernández, Manuel Antonio; Andrada Borzollino, Marisa Ana; Bernaldo De Quirós Miranda, Yara; Fernández Rodríguez, Antonio Jesús (2008)
Collisions between large vessels and cetaceans have only recently been fully recognized as a source of anthropogenic mortality and injury, and they need to be assessed and quantified. A pathological diagnosis of the primary cause of death is not always easy, as most of the carcasses are found in a very advanced process of decomposition. Floating carcasses can be stroken by vessels, making difficult to determine whether the collision had occurred pre- or post-mortem. Since some years ago, we have made efforts for the development of histochemical tecniques that could help to differentiate those situations, allowing us to get a final diagnosis. A histochemical technique based on detecting fat emboli in the lung blood vessels has been set up, and it has been applied to whales suspected to be killed by ship collision. An example of a collision of fin whale (Balaenoptera physalus) and a cargo-ship is presented in this poster. This animal appeared draping over the bow bulb of a big vessel at the commercial port of Las Palmas de Gran Canaria. Necropsy was carried out, showing severe damaging in several parts of the body and internal organs. Numerous fat emboli were demonstrated within mid size vessels and capillaries using osmium tetroxide and Oil Red O histochemical techiques. The present results reestate that both histochemical techniques could be a valid forensic tool to demonstrate severe traumas occurred "in vivo" (especially in ship-collision cases), allowing us to rule out "postmortem" changes found during the necropsy.